2012
DOI: 10.3989/cyv.462012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of La<sub>1-x</sub> Ca<sub>x</sub> Al O<sub>3</sub>

Abstract: La 1 -x Ca x Al O 3 (0 ≤ x ≤ 0.6) perovskite-type oxides were prepared by co-precipitation method using metal nitrate salts as cation precursors and NaOH solution as the precipitating agent. Differential thermal analysis (DTA) and thermogravimetric analysis (TGA) results indicate that decomposition of the precursor to the oxide begins at ~ 800°C. Powder X-ray diffraction (XRD) patterns confirm the formation of the perovskite phase. Both undoped and doped lanthanum aluminates show two IR active vibrational mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The formation of agglomerate is probably due to the nature of the solvent used in the preparation of the precipitate [47]. Similar tendency has been found previously for samarium-doped ceria powders [48], La 1-x Ca x AlO 3 oxides [4], LaAl 1-x Ni x O 3 oxides [30]. It has been shown that treating the precipitate with water and ethanol allows interactions between particles which lead during drying to the formation of chemical bonds.…”
Section: Structural and Morphological Characterizationsupporting
confidence: 59%
“…The formation of agglomerate is probably due to the nature of the solvent used in the preparation of the precipitate [47]. Similar tendency has been found previously for samarium-doped ceria powders [48], La 1-x Ca x AlO 3 oxides [4], LaAl 1-x Ni x O 3 oxides [30]. It has been shown that treating the precipitate with water and ethanol allows interactions between particles which lead during drying to the formation of chemical bonds.…”
Section: Structural and Morphological Characterizationsupporting
confidence: 59%
“…The biaxial stress along the lateral and longitudinal directions with 2D area detector using a standard 2ϴ sin2Ѱ method [19]. The average grain size of the coatings was determined from Xray peak broadening by applying the Scherrer formula [20,21]:…”
Section: Coating Characterizationmentioning
confidence: 99%
“…Scherrer's formula is used for the determination of the Crystallite sizes of the coatings from the X-ray peak broadening of the (330) diffraction peak [9,10,11,19]:…”
Section: Coating Characterizationmentioning
confidence: 99%